Effects of Mesalamine Treatment on Gut Barrier Integrity After Burn Injury. Issue 5 (September 2016) - Cannon, Abigail R.; Akhtar, Suhail; Hammer, Adam M.; Morris, Niya L.; Javorski, Michael J.; Li, Xiaoling; Kennedy, Richard H.; Gamelli, Richard L.; Choudhry, Mashkoor A.
Abstract : Gut barrier disruption is often implicated in pathogenesis associated with burn and other traumatic injuries. In this study, the authors examined whether therapeutic intervention with mesalamine (5-aminosalicylic acid [5-ASA]), a common anti-inflammatory treatment for patients with inflammatory bowel disease, reduces intestinal inflammation and maintains normal barrier integrity after burn injury. Male C57BL/6 mice were administered an approximately 20% TBSA dorsal scald burn and resuscitated with either 1 ml normal saline or 100 mg/kg of 5-ASA dissolved in saline. The authors examined intestinal transit and permeability along with the levels of small intestine epithelial cell proinflammatory cytokines and tight junction protein expression 1 day after burn injury in the presence or absence of 5-ASA. A significant decrease in intestinal transit was observed 1 day after burn injury, which accompanied a significant increase in gut permeability. The authors found a substantial increase in the levels of interleukin (IL)-6 (by ~1.5-fold) and IL-18 (by ~2.5-fold) in the small intestine epithelial cells 1 day after injury. Furthermore, burn injury decreases the expression of the tight junction proteins claudin-4, claudin-8, and occludin. Treatment with 5-ASA after burn injury prevented the burn-induced increase in permeability, partially restored normal intestinal transit, normalized the levels of the proinflammatory cytokines IL-6 and IL-18, and restored tight junction protein expression of claudin-4 and occludin compared with that of sham levels. Together these findings suggest that 5-ASA can potentially be used as treatment to decrease intestinal inflammation and normalize intestinal function after burn injury.